Input–output methods of energy analysis. (4th August 2014) - Peet, John
Input–output energy analysis (IOEA) is a specific application of economic input–output analysis which is useful in tracing the energy components of inputs to manufacturing or other economic processes. Input–output techniques provide valuable means of linking physical with economic factors in an economy, especially when modified into the IOEA form, which explicitly incorporates the use of primary energy.